2022
DOI: 10.3390/antiox12010091
|View full text |Cite
|
Sign up to set email alerts
|

Epilobium Species: From Optimization of the Extraction Process to Evaluation of Biological Properties

Abstract: Epilobium species are used in Romanian folk medicine as tinctures, tea, or tablets for ameliorating the symptoms of benign prostate hyperplasia (BPH), but scientific-based evidence is scarce for this species or other endemic plants of the same genus. Therefore, the aims of this research were to evaluate the phytochemical profile of five endemic Epilobium species (E. hirsutum L., E. parviflorum Schreb., E. palustre L. E. dodonaei Vill., and E. angustifolium L.) and to assess their in vitro biological activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…However, these extracts still had a higher antioxidant activity than those reported O N L I N E F I R S T in the literature. Vlase et al (2023) applied ultrasonic-assisted extraction on 30% (v/v) ethanol extracts of hoary willowherb and achieved around 90 mM TE/L extract using the ABTS method. These authors reported the total phenolic content of the same extract of approximately 5 mg GAE/mL extract (Vlase et al, 2023).…”
Section: Antioxidant Capacity Of Aqueous Herbal Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these extracts still had a higher antioxidant activity than those reported O N L I N E F I R S T in the literature. Vlase et al (2023) applied ultrasonic-assisted extraction on 30% (v/v) ethanol extracts of hoary willowherb and achieved around 90 mM TE/L extract using the ABTS method. These authors reported the total phenolic content of the same extract of approximately 5 mg GAE/mL extract (Vlase et al, 2023).…”
Section: Antioxidant Capacity Of Aqueous Herbal Extractsmentioning
confidence: 99%
“…Vlase et al (2023) applied ultrasonic-assisted extraction on 30% (v/v) ethanol extracts of hoary willowherb and achieved around 90 mM TE/L extract using the ABTS method. These authors reported the total phenolic content of the same extract of approximately 5 mg GAE/mL extract (Vlase et al, 2023). For comparison, the average antioxidant activity of our hoary willowherb extracts was 4•10 5 mM TE/L, while the total phenolic content was around 35 mg GAE/mL extract on average.…”
Section: Antioxidant Capacity Of Aqueous Herbal Extractsmentioning
confidence: 99%
“…Knowledge concerning indigenous Epilobium species remains incomplete and insufficient. This gap is particularly noteworthy given the abundance of these traditionally used medicinal plants within Romania’s native flora [ 27 ]. Considering that even minor variations in chemical composition can lead to significant disparities in bioactivity [ 20 , 21 , 28 ], the limited availability of scientifically supported data regarding Romania’s native flora poses a substantial limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed a growing interest in the phytochemistry of Epilobium plants, commonly known as willow herbs [ 27 , 29 , 30 ], supported by recent discoveries highlighting their beneficial effects in various health conditions, most notably in the prevention and treatment of prostate ailments [ 31 , 32 ]. Traditional folk medicine practices have long used the properties of willow herb infusions in managing benign prostate hyperplasia (BPH), prostatitis, as well as disorders of the bladder, kidneys, and urinary tract [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation